(untitled) (Global Journal of Medical Research, 2013)
Background: Renal cell carcinoma (RCC) is most commonprimary tumour of kidney in adult, responsible for (80-85%) of renal tumour(1). Due to ultimately absence of studies in Sudan in assessing the pattern and presentation of RCC, we conducted this study in Gezira Hospital for renal diseases and Surgery, in period from January 2006- January 2012. Objective: To determine the clinical presentation, pathological pattern and stages of RCC in patients who treated in (GHRS). Results: A total of 60 patients were diagnosed to have RCC in duration of 5 years. The disease is more common in male, with peak incidence in the fifth and sixth decades. Incidentally diagnosed are 6 patients. Classical triad observed in 19patients .Mean duration of symptoms was 4 months. Some patients had metastasis in the lung, bones or liver when diagnosed. Most of the patients presented with loin mass, small number with cervical lymphadenopathy, lower limb edema or non reduciblevaricocele